The Bakkie Brigade in Cape Town’s urban waste economy: exploring waste mobilities and the precariat - Goeiman, Johnathan (University of the Western Cape, 2021)
Magister Artium - MA === Solid waste management in South Africa is in a phase of transitioning. This transition entails the valorisation and diversion of recyclable waste away from landfills for the creation of a new secondary recycling economy. However, reclaimers within the Global South have been engaged in valorising waste through market-driven pricing. Localised and ‘informal’ as they are, they remain a significant source of labour for global capital. Their presence runs parallel to the emergence of green models such as the circular economy, coupled with contentious initiatives that aim at formalising and integrating reclaimers. Given the revitalised emphasis on the urban waste economy, inadequate attention has been given to understanding the linkages between the formal processing companies and informal waste reclaimers operating at the level of the street and landfill.